The legal framework of apostasy in Egypt: an illegal limitation on freedom of belief - Nassar, Yara Yasser (AUC Knowledge Fountain, 2014)
In 1996 the Egyptian Court of Cassation annulled the marriage of scholar Nasr Hamed Abou Zayd. The court ruled that through his blasphemous religious statements, he had committed apostasy. Four decades later, in 2007 the Egyptian Administrative Court did not recognize the conversion of 22 citizens from Islam to Christianity considering it an act of apostasy not recognizable by Islamic Shari'a. Egyptian authorities have arrested citizens converting from Islam citing that their apostasy was considered a belittlement of Islam and hence a violation of Egyptian Criminal Law. These are but just three examples and simply the tip of the iceberg of the legal framework of apostasy in Egyptian law and its effect on the lives of citizens and their right to freedom of belief and worship. This thesis will analyze limitations on freedom of belief in Egypt through an analysis of the legal framework of the right to abandon Islam, apostasy. In the Thesis, through a thorough analysis of Egyptian jurisprudence in regards to apostasy, we will understand that Egyptian judges wrongfully consider the rules of apostasy as an undisputed part of Islamic Shari’a and therefore a part of Egyptian public policy that is legally binding. The Diversity of opinion in Islamic Shari’a in regards to apostasy will be analyzed to prove that its rules are in fact disputed and should not be applied as part of Egyptian public policy. The Thesis will then move to see the danger of the legal framework of apostasy as it is used for political means. Finally, after understanding the framework of apostasy we will attempt to understand the choice of the Egyptian judges to apply the most conservative understanding of Islamic Shari’a in regards to apostasy and consequently choose to limit freedom of belief and violate Egypt’s international obligations.